Analysis of test results of a household absorption refrigerating appliance on an electric and gas source of thermal energy - Adambayev, Daniyorbek; Titlov, Alexander (Technology audit and production reserves, 2021)
One of the biggest challenges for refrigeration systems is their conversion to environmentally friendly refrigerants. This attracts the attention of developers of household refrigeration equipment to absorption refrigeration devices (ARD), which include an absorption refrigeration unit (ARU). ARD working fluid consists of natural components - ammonia water solution with the addition of an inert gas (hydrogen). Therefore, the use of ARU can be considered as one of the options for transferring to environmentally friendly refrigerants. In recent years, in connection with the rapidly developing gasification of the population of Europe, an alternative has arisen - the operation of household ARD on natural gas. Natural gas can become an alternative to electrical energy in stationary operating conditions of household refrigeration appliances. Thus, the object of the study was a single-chamber household refrigerator with a low-temperature compartment "Kiev-410" (Ukraine). In this paper, the study is aimed at comparing the thermal modes of operation and the costs of operating a household ARD on electric energy and natural gas. To solve this, it was necessary to determine the temperatures at the characteristic points of the refrigeration apparatus and in the chamber, as well as the energy consumption of the absorption-type apparatus in accordance with regulatory documents, at various values of the thermal load on the thermosyphon and various ambient temperatures. The studies were carried out at elevated outdoor temperatures: 28–33 ° С. The range of thermal loads on the ARU thermosyphon electric heater was 50–130 W. The range of numerical values of natural gas consumption in the burner was (2.8–8.8) • 10-6 m3/s. In the process of conducting experimental studies of household ARD, results were obtained showing the economic prospects of working in stationary conditions on natural gas. At the same time, ARD of increased useful volume (200 dm3 and above) has the greatest prospects. The daily operating costs in them are 0.078...0.084 USD, which is 23...27 % lower than the case of using electricity. When the ARU thermosyphon is built into the heating and hot water supply system, it becomes possible to use the temperature potential of the waste products of combustion and completely eliminate operating costs.